Turismo cultural na ZEPH-Ribeira: possibilidades e limitações - Ferraz, Valéria de Souza (2008)
Considering that urban interventions, planned and executed recently at Natal, RN, should put Ribeira - one of the town centers - in the new limits of the expanded center of the city, this work examines the use of this new accessibility for the benefit of the development of an infrastructure to support a type of tourism currently seen as an alternative to diversification into areas dominated by entertainment tourism (the case of Natal). A local with city's traditional cultural facilities and holder of a set built that is a synthesis of the images of the neighborhood, it fears that this increase in the potential for movement and flows of use stimulate speculation and deployment of a bulk type of activity incompatible with the preservation the architectural heritage. Important economy for the city, tourism has been showing a factor propellant processing urban related changes in accessibility. It is argued that cultural tourism, often used in plans and projects of revitalization across the country, may be factor for sustainable development and conserve the assets, and contributes to the process of revitalization of the historic cultural center as Ribeira. Intended to illustrate the need to consider other information that might help in the revitalization of the neighborhood, this research presents the offer cultural tourism of Ribeira and identifies and maps certain physical attributes that, combined with functional attributes, can stimulate or inhibit the diversity and vitality in the region